Preparation method of three-dimensional porous carbon block electrode based on polymer material
Through the use of zinc -based thermal solution auxiliary agents during the preparation of porous carbon materials, the transformation of carbonization process is solid, and the problem of lack of performance in the application of multi -porous carbon materials in the application of high surface area needs, and the preparation of high -performance multi -porous carbon materials is achieved. The craftsmanship and reduced costs.
Patent Information
- Application Number
- CN202411589485.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-24
AI Technical Summary
It is difficult to accurately control the pore structure during the preparation process of existing porous carbon materials, resulting in insufficient performance in applications with high surface area requirements, and complex preparation process and high cost.
A three-dimensional porous carbon bulk electrode preparation method based on polymer materials is used. By adding a zinc-based pyrolysis auxiliary agent to the carbon source, zinc oxide is generated during the pyrolysis process, and the carbonization process of the carbon source material is changed from a molten state to a solid state. Suppress the melt flow of polymer materials to prepare porous carbon materials with excellent mechanical and chemical stability.
It has improved the porous carbon material ratio and structural design flexibility, simplifies the preparation process, reduces costs, and enhances the mechanics and chemical stability of the material. It is suitable for electrochemical energy storage and electrical catalytic fields.
Smart Images

Figure CN119349575A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous carbon materials, and in particular to a method for preparing a three-dimensional porous carbon block electrode based on polymer materials. Background Art
[0002] Porous carbon materials have excellent physical and chemical properties, such as high specific surface area, good electrical conductivity, chemical stability and adjustable pore structure, making them ideal materials for energy conversion and storage devices (such as supercapacitors, lithium-ion batteries, fuel cells, etc.). The extremely high specific surface area provides a place for chemical and electrochemical reactions, the conjugated π bonds give them excellent electrical conductivity, the stable carbon-carbon bonds ensure their good chemical stability against high temperature, corrosion and chemical reactions, the precisely adjustable pore structure expands their specific application needs in different fields, and the convenient chemical modification, heteroatom doping and composite properties with other materials improve their catalytic activity, making porous carbon materials perform well in adsorption and energy storage applications, especially in capacitors, battery electrodes and catalyst carriers.
[0003] The physical and chemical properties of porous carbon materials are closely related to the design of their three-dimensional pore structure. Their preparation methods can be divided into the following categories: (1) Template method, in which a carbon source and a template are mixed, and carbon materials are obtained by high-temperature pyrolysis or other methods. The template material is removed by physical or chemical methods to form a pore structure in the obtained carbon material, and the size, shape and distribution of the pores are precisely controlled. Among them, the hard template method using inorganic solid materials (such as silica, alumina) as templates has a stronger ability to control the pores. For example, patent CN103738935A discloses a method for preparing porous carbon materials using porous copper as a template. However, this method generally requires post-processing methods such as chemical methods to remove the template. The soft template method using organic materials (such as surfactants, block copolymers) can generally directly obtain porous carbon materials, but the ability to accurately control the pore structure is poor; (2) Hydrothermal synthesis method (solvothermal synthesis method) uses hydrothermal reaction to convert the precursor into the desired porous carbon material under high pressure and high temperature. It can usually convert biomass materials into porous carbon under mild conditions. It is environmentally friendly and renewable, and is suitable for the preparation of carbon materials with specific microporous and mesoporous structures. However, the shape control performance of the macroscopic block is poor, and it is difficult to obtain porous carbon block materials with custom shapes. In the hydrothermal synthesis method, the water solvent is replaced by an organic solvent, which is called the solvothermal synthesis method. Its advantages and disadvantages are similar to those of the hydrothermal synthesis method. (3) The carbonized biomass method prepares porous carbon materials by directly pyrolyzing biomass materials of plant or animal origin (such as coconut shells, wood chips, corn stalks, etc.) at high temperature, retaining the pore structure therein. It has the advantages of environmental protection and low cost, but the pore controllability is poor. (4) The high-temperature pyrolysis method directly pyrolyzes the carbon source material or uses a physical activator (such as carbon dioxide, water vapor) / chemical activator (such as potassium hydroxide, phosphoric acid) to assist in pyrolysis in an inert atmosphere at high temperature to form a porous structure. It has the advantages of a wide range of precursor choices (including polymer compounds, resins and biomass), simple post-processing, and low cost, but the controllability of microscopic pores is poor.
[0004] The physical and chemical properties of porous carbon materials are also closely related to their geometric size. According to their size, they can be divided into two categories: powder porous carbon materials and bulk porous carbon materials. Powder porous carbon materials usually have a higher specific surface area and have higher reactivity and selectivity in applications such as adsorption and catalysis. Their smaller size is conducive to good dispersion in solution and improved utilization efficiency. However, due to the lack of a clear shape and structural support, the mechanical strength and stability of powder porous carbon materials are usually poor, and in some applications, such as when used as a catalyst in a fixed bed reactor, the powder form may make it difficult to fix and recycle; when used as an electrode material for secondary batteries and electrochemical reactions, powder porous carbon materials usually need to be used in combination with conductive agents, binders and other components, which not only reduces the energy density, but also affects the structural stability of the electrode material during ion insertion / extraction during charging and discharging. Bulk porous carbon materials make up for the above shortcomings. Their good mechanical strength and stability are suitable for applications that require fixation and support. The clear bulk structure makes it more convenient to assemble and fix than powder form, and it can withstand higher pressure when used as a catalyst in a fixed bed reactor. When used as an electrochemical electrode, the three-dimensional interconnected conductive structure is conducive to long-term electron transmission, so that the addition of components such as conductive agents and binders can be omitted, the energy density can be improved, and it usually shows better stability during long-term use and circulation in the energy and environmental fields. However, the specific surface area of bulk porous carbon materials is usually lower than that of powder form, which may affect its performance in applications with high surface area requirements such as adsorption and catalysis, and compared with powder porous carbon materials, the preparation of bulk porous carbon materials may require more complex processes and equipment.
[0005] In general, compared with powdered porous carbon materials, bulk porous carbon materials have better mechanical stability and chemical stability and a wider range of applications, but their specific surface area needs to be improved, the preparation process needs to be simplified, the pore structure needs to be further precisely controlled, and the cost needs to be reduced. It is urgent to develop a new preparation process to obtain high-performance three-dimensional porous carbon bulk materials. Summary of the invention
[0006] The present invention provides a method for preparing a three-dimensional porous carbon block electrode based on a polymer material. A pyrolysis auxiliary agent is added to a carbon source. Zinc oxide is generated during the pyrolysis process to transform the carbonization process of the carbon source material from a molten state to a solid state, thereby inhibiting the melt flow of the polymer material. The obtained block porous carbon material has excellent mechanical stability and chemical stability.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a three-dimensional porous carbon block electrode based on polymer materials comprises the following steps: mixing a carbon source with a pyrolysis auxiliary agent to prepare a block precursor with a custom target shape; heating the block precursor to above 1000°C in a protective atmosphere to obtain a three-dimensional porous carbon material block with a custom target shape; the carbon source is a thermoplastic polymer, and the pyrolysis auxiliary agent is selected from one or more of zinc group metal oxide powder, zinc group metal nitrate powder, and zinc group metal carbonate powder.
[0008] Preferably, the thermoplastic polymer is selected from one or more of polyethylene, polypropylene, polybutadiene, polyisoprene, polystyrene, polyacrylate, polylactic acid, polyacrylonitrile-polybutadiene-polystyrene copolymer / blend, and thermoplastic polyurethane.
[0009] Preferably, the particle size of the pyrolysis auxiliary agent is 10 nm - 100 μm.
[0010] Preferably, the carbon source is directly mixed with the pyrolysis auxiliary agent to form a block precursor with a custom target shape. The direct mixing method has a simple process, high production efficiency, and is suitable for continuous production.
[0011] Preferably, the carbon source and the pyrolysis auxiliary agent are fully mixed in an organic solvent and then dried to form a block precursor with a custom target shape. The liquid phase mixing method has good dispersibility, excellent process consistency, and more stable product performance.
[0012] Preferably, the organic solvent is selected from one or more of methanol, ethanol, acetic acid, ether, ethyl acetate, ethylene glycol, isopropanol, n-butanol, isobutanol, propyl ether, acetone, tetrahydrofuran, n-hexane, cyclohexane, heptane, isooctane, petroleum ether, benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0013] Preferably, the method of making the bulk precursor into a custom target shape is casting, molding, extrusion, injection molding or calendaring.
[0014] Preferably, the protective atmosphere is selected from one or more of nitrogen, argon and helium.
[0015] Preferably, the mass ratio of carbon source to pyrolysis auxiliary agent is (0.8-1.5): 1. A high mass ratio of carbon source is beneficial to the processing of the precursor, but will lead to softening and shaping difficulties during the pyrolysis process, as well as a decrease in the specific surface area of the carbon product; a low mass ratio of carbon source is beneficial to increasing the specific surface area of the final product, but will limit the processing methods, such as extrusion, injection molding, calendaring, etc., which require a certain degree of viscoelasticity.
[0016] Preferably, the heating step is: heating to 1100-1200°C at a rate of 3-20°C / min and keeping the temperature for 2-3h.
[0017] Preferably, the heating steps are: heating to 300°C at a heating rate of 10-20°C / min, and keeping warm for 20-40min; then heating to 500°C at a heating rate of 4-6°C / min, and keeping warm for 50-70min; then heating to 1000°C at a heating rate of 3-5°C / min, and keeping warm for 50-70min; then heating to 1200°C at a heating rate of 5-7°C / min, and keeping warm for 120-160min; finally naturally cooling to room temperature.
[0018] The principle of the present invention is that the zinc-based pyrolysis auxiliary agent mainly plays the role of pore formation, activation, catalytic graphitization, and geometric structure finalization. Its essence is that the zinc-based pyrolysis auxiliary agent decomposes to generate zinc oxide and releases corresponding gases during the heating process, and the released gases will form certain pores. In the range of 300-500 ℃, zinc oxide promotes the dehydrogenation reaction and condensation reaction of the polymer material and forms a charred material, inhibits the melt flow of the polymer material, and changes the polymer material from molten carbonization to solid carbonization, retaining the geometric configuration of the precursor; in the range of 500-1000 ℃, zinc oxide and the polymer precursor undergo a carbon thermal reduction reaction (C + ZnO → CO↑+ Zn), generating a large number of pores and zinc elements. When the temperature further increases to above 900 ℃, the zinc element evaporates and is taken away from the pyrolysis area by the protective gas; in the range above 1000 ℃, the elimination of heteroatoms and the deep graphitization reaction of carbon materials mainly occur. Therefore, by combining different heating steps at different stages, the specific surface area of the carbon material block can be further improved, resulting in better mechanical stability and chemical stability of the bulk porous carbon material.
[0019] The three-dimensional porous carbon block electrode prepared by the present invention is a hierarchical porous block structure connected by petal-shaped spherical units. The lowest level is a layered carbon structure formed by chemical etching with a pyrolysis auxiliary agent, which provides active sites for electrochemical reactions; the second is a porous spherical unit structure formed by a pyrolysis auxiliary agent, which provides a channel for material transmission; the highest level is a macroscopic three-dimensional porous block, and the continuous block structure is conducive to the transmission of electrons and phonons.
[0020] The beneficial effects of the present invention are: (1) The selection range of high-performance porous carbon material precursors has been expanded, and single-component or multi-component polymer materials can be selected; newly synthesized polymer material resins, newly processed plastics / rubbers / fibers / coatings / adhesives containing additives, and recycled polymer waste can be selected. The selection range of carbon source precursors is wide, and the flexibility of structural regulation is high.
[0021] (2) The flexibility of the structural design of porous carbon materials is improved. The pore size, porosity, pore distribution, internal specific surface area, and degree of graphitization of porous carbon materials can be arbitrarily controlled by zinc-based pyrolysis auxiliary agents; the macroscopic geometric shape of porous carbon blocks can be arbitrarily customized by processing precursors; the composition and heteroatom doping of porous carbon materials can be determined by the type of precursors, which is conducive to their application in electrochemical energy storage, electrocatalysis, molecular adsorption and other fields.
[0022] (3) The geometric structure stability of the porous carbon block material design is improved. The zinc oxide in the pyrolysis process can transform the carbonization process of the carbon source material from a molten state to a solid state, inhibiting the melt flow of the polymer material. The resulting product maintains the geometric shape of the precursor, avoiding the problems of low mechanical strength, low stability, difficulty in fixation and recycling of powdered porous carbon, which is conducive to its application in electrocatalysis, sewage treatment, molecular adsorption and other fields.
[0023] (4) The economic efficiency of the preparation of porous carbon materials is improved. The carbon source can be recycled plastic waste. The zinc element generated during the carbon thermal reduction process of pyrolysis can be cooled with the protective gas and collected in the exhaust gas treatment device for recycling, thereby reducing the cost of preparing porous carbon materials.
[0024] (5) The environmental friendliness of the preparation of porous carbon materials is improved. The zinc-based pyrolysis auxiliary agent can be spontaneously removed during the pyrolysis process, without the need for post-treatment steps such as pickling. This avoids wastewater treatment during the pickling process and damage to pipelines and equipment caused by corrosive gases, greatly reducing the pollution to the environment and the health hazards to process operators throughout the entire process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the preparation process of the three-dimensional porous carbon block electrode material of the present invention.
[0026] Figure 2 These are photos of the preparation process of the three-dimensional porous carbon block electrode material of the present invention.
[0027] Figure 3 This is a scanning electron microscope image of the three-dimensional porous carbon block product prepared in Example 1.
[0028] Figure 4 The three-dimensional porous carbon block products prepared in Example 1 and Comparative Example 1 are shown in the cycling performance when used as negative electrodes of sodium ion batteries.
[0029] Figure 5 This is a scanning electron microscope image of the three-dimensional porous carbon product prepared in Comparative Example 2.
[0030] Figure 6 This is a scanning electron microscope image of the three-dimensional porous carbon block product prepared in Example 2.
[0031] Figure 7 This is the pore size distribution diagram of the three-dimensional porous carbon block product prepared in Example 3. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through specific embodiments.
[0033] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are by weight, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0034] Example A method for preparing a three-dimensional porous carbon block electrode based on polymer materials, such as Figure 1 As shown, the following steps are included: (1) The carbon source is mixed with a pyrolysis auxiliary agent to form a bulk precursor with a customized target shape.
[0035] The carbon source is a thermoplastic polymer, and the thermoplastic polymer is selected from one or more of polyethylene, polypropylene, polybutadiene, polyisoprene, polystyrene, polyacrylate, polylactic acid, polyacrylonitrile-polybutadiene-polystyrene copolymer / blend, and thermoplastic polyurethane.
[0036] The pyrolysis auxiliary agent is selected from one or more of zinc group metal oxide powder, zinc group metal nitrate powder and zinc group metal carbonate powder. The particle size of the pyrolysis auxiliary agent is 10nm - 100μm.
[0037] The carbon source and the pyrolysis auxiliary agent can be directly mixed to form a bulk precursor of a custom target shape. The direct mixing method has a simple process, high production efficiency, and is suitable for continuous production. The carbon source and the pyrolysis auxiliary agent can also be fully mixed in an organic solvent and dried to form a bulk precursor of a custom target shape. The liquid phase mixing method has good dispersibility, excellent process consistency, and more stable product performance. The organic solvent is selected from one or more of methanol, ethanol, acetic acid, ether, ethyl acetate, ethylene glycol, isopropanol, n-butanol, isobutanol, propyl ether, acetone, tetrahydrofuran, n-hexane, cyclohexane, heptane, isooctane, petroleum ether, benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
[0038] The mass ratio of carbon source to pyrolysis auxiliary agent is (0.8-1.5): 1. A high mass ratio of carbon source is beneficial to the processing of the precursor, but it will lead to softening and shaping difficulties during the pyrolysis process, as well as a decrease in the specific surface area of the carbon product; a low mass ratio of carbon source is beneficial to increasing the specific surface area of the final product, but it will limit the processing methods, such as extrusion, injection molding, calendering, etc., which require a certain degree of viscoelasticity.
[0039] Methods for making bulk precursors into customized target shapes include, but are not limited to, casting, molding, extrusion, injection molding, or calendaring.
[0040] (2) The bulk precursor is heated to above 1000 °C in a protective atmosphere to obtain a three-dimensional porous carbon material block with a customized target shape.
[0041] The protective atmosphere includes, but is not limited to, one or more of nitrogen, argon, and helium.
[0042] The heating step is: heating to 1100-1200°C at a rate of 3-20°C / min, and keeping the temperature for 2-3 hours. As a further preferred step, the heating step is: heating to 300°C at a heating rate of 10-20°C / min, and keeping the temperature for 20-40 minutes; then heating to 500°C at a heating rate of 4-6°C / min, and keeping the temperature for 50-70 minutes; then heating to 1000°C at a heating rate of 3-5°C / min, and keeping the temperature for 50-70 minutes; then heating to 1200°C at a heating rate of 5-7°C / min, and keeping the temperature for 120-160 minutes; and finally cooling naturally to room temperature.
[0043] like Figure 2 The precursor can be processed into shapes such as discs, petals, cylinders, and cuboids. The final three-dimensional porous carbon material block product can maintain the geometric shape of the precursor. The obtained porous carbon block can be used as a special-shaped electrode for electrochemical energy storage, electrocatalysis, sewage treatment, molecular adsorption, friction power generation, fluid flow power generation and other fields.
[0044] Example 1 A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1. Take 6 g of polyacrylonitrile-polybutadiene-polystyrene copolymer resin, mix it with 5 g of zinc oxide powder (particle size 500 nm) in N,N-dimethylformamide, stir and heat to 100 °C until the solvent evaporates to obtain a milky white block solid; Step 2. Pressing the solid obtained in step 1 into a disc-shaped precursor using a tablet press at room temperature; Step 3. Place the disc-shaped precursor obtained in step 2 in a tubular furnace for pyrolysis, using argon as the protective gas, with a flow rate of 50 mL / min and a heating rate of 5 °C / min. After heating to 1200 °C and keeping it warm for 2 h, a disc-shaped three-dimensional porous carbon block material can be obtained after natural cooling.
[0045] Figure 3 This is a scanning electron microscope image of the three-dimensional porous carbon block product prepared in Example 1. Figure 3 The porous carbon block material obtained is a hierarchical porous block structure connected by petal-shaped spherical units. The lowest level is the layered carbon structure formed by chemical etching of zinc oxide, which provides active sites for electrochemical reactions; the second is the porous spherical unit structure formed by zinc oxide auxiliary agents, which provides channels for material transmission; the highest level is a macroscopic three-dimensional porous block, and the continuous block structure is conducive to the transmission of electrons and phonons. Due to the carbon thermal reduction reaction and activation of zinc oxide, the pore structure on the spherical unit is enriched, the specific surface area is increased, and it is conducive to the chemical reaction and electrochemical reaction. The specific surface area of the obtained block porous carbon material is moderate, and its hierarchical porous structure is particularly suitable for use as a negative electrode material for secondary batteries in electrochemical energy storage. The layered carbon structure is conducive to the reversible insertion / extraction of lithium, sodium, potassium, calcium and other ions and the improvement of cycle stability. The open spherical unit structure is conducive to the rapid transportation of electrolytes and the improvement of rate performance. The interconnected porous structure and the complete macroscopic block are conducive to the transmission of electrons and the increase of reversible specific capacity.
[0046] The specific surface area of the carbon material obtained in Example 1 was 120 m 2 / g. X-ray photoelectron spectroscopy test shows that the oxygen impurity content is less than 2% and the zinc impurity content is less than 1%, which proves the spontaneous removal of the zinc-based pyrolysis auxiliary agent. The zinc-based auxiliary agent can be regenerated in the tail gas treatment device, and the recovery rate of the auxiliary agent zinc oxide in Example 1 can reach more than 80%.
[0047] Example 2 A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1: Take 7 g of polystyrene resin and mix it with 5 g of zinc oxide powder (particle size 50 nm) in N,N-dimethylformamide, stir and heat to 80 °C until the solvent partially evaporates to obtain a milky white viscous fluid; Step 2: Pour the fluid obtained in step 1 into a petal-shaped mold and further dry it until the solvent is completely evaporated to obtain a petal-shaped precursor; Step 3: The petal-shaped precursor obtained in step 2 is placed in a tubular furnace for pyrolysis, with argon as the protective gas, a flow rate of 50 mL / min, a heating rate of 5 °C / min, and the temperature is raised to 1100 °C and kept for 2.5 h. After natural cooling, a petal-shaped three-dimensional porous carbon block material can be obtained.
[0048] Figure 6 This is a scanning electron microscope image of the three-dimensional porous carbon block product obtained in Example 2, showing the microscopic porous structure inherited from the nano zinc oxide pyrolysis auxiliary agent. According to the nitrogen adsorption and desorption test, the specific surface area of the carbon material obtained in Example 2 is 860 m 2 / g, and the obtained pore size is mainly mesopores.
[0049] Example 3 A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1: Take 5 g of the recovered polyacrylonitrile resin and mix it with 5 g of zinc oxide powder (particle size 90 nm) in N,N-dimethylformamide, stir and heat to 100 °C until the solvent is completely evaporated to obtain a milky white solid; Step 2: placing the solid obtained in step 1 into a circular mold and hot pressing it into a circular sheet; Step 3: Place the circular flakes obtained in step 2 in a tubular furnace for pyrolysis, using nitrogen as the protective gas with a flow rate of 100 mL / min and a heating rate of 5 °C / min. After heating to 1200 °C and keeping the temperature for 3 h, a circular three-dimensional porous carbon block material can be obtained after natural cooling.
[0050] Figure 7 : is the pore size distribution data of the three-dimensional porous carbon block product prepared in Example 3. According to the nitrogen adsorption and desorption test, the specific surface area of the porous carbon material prepared in Example 3 is 1050 m 2 / g, and the high specific surface area is conducive to being used as an electrode material in supercapacitors. The specific surface area of the porous carbon material can be adjusted according to the needs by the type and size of the precursor and the zinc-based pyrolysis auxiliary agent.
[0051] Example 4 A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1: Take 6.5 g of the recycled polyethylene and mix it with 5 g of zinc carbonate powder in toluene, stir and heat to 80°C until the solvent is completely evaporated to obtain a white solid mixture; Step 2: placing the mixture obtained in step 1 into a micro injection molding machine and injection molding it into a cuboid; Step 3: The precursor obtained in step 2 is placed in a tubular furnace for pyrolysis, using argon as the protective gas with a flow rate of 100 mL / min and a heating rate of 5 °C / min. After heating to 1200 °C and keeping the temperature for 2 h, a rectangular three-dimensional porous carbon block material can be obtained after natural cooling.
[0052] The three-dimensional porous carbon material block product finally obtained in Example 4 can maintain the geometric shape of the precursor. According to the nitrogen adsorption and desorption test, the specific surface area of the carbon material obtained in Example 4 is 280 m 2 Example 4 illustrates that the recycled polymer material carbon source can also be used to prepare a three-dimensional porous carbon block.
[0053] Example 5 The difference from Example 1 is that the mass ratio of polyacrylonitrile-polybutadiene-polystyrene copolymer resin to nano zinc oxide is 0.8:1. That is, in step 1, 4 g of polyacrylonitrile-polybutadiene-polystyrene copolymer resin is mixed with 5 g of zinc oxide powder (particle size 500 nm). The specific surface area of the obtained three-dimensional porous carbon block material is 250 m 2 / g.
[0054] Example 6 The difference from Example 1 is that the mass ratio of polyacrylonitrile-polybutadiene-polystyrene copolymer resin to nano zinc oxide is 1.5:1. That is, in step 1, 7.5 g of polyacrylonitrile-polybutadiene-polystyrene copolymer resin is mixed with 5 g of zinc oxide powder (particle size 500 nm). The specific surface area of the obtained three-dimensional porous carbon block material is 50 m 2 / g.
[0055] Comparing Example 1, Example 5 and Example 6, as the mass ratio of the carbon source increases, the specific surface area of the obtained carbon material block gradually decreases.
[0056] Example 7 The difference from Example 1 is that different heating rates are used in different stages in step 3. That is, the heating process in step 3 is: heating to 300 °C at a heating rate of 20 °C / min at room temperature, and keeping warm for 30 min; then heating to 500 °C at a heating rate of 4 °C / min, and keeping warm for 60 min; then heating to 1000 °C at a heating rate of 3 °C / min, and keeping warm for 60 min; then heating to 1200 °C at a heating rate of 5 °C / min, and keeping warm for 120 min; finally cooling naturally to room temperature. The specific surface area of the obtained three-dimensional porous carbon block material is 190 m 2 / g.
[0057] Comparing Example 1 and Example 7, after staged heating, the polymer can undergo more complete dehydrogenation and condensation reactions in the range of 300-500°C, and the coke intermediate product can achieve more complete activation reactions through carbon thermal reduction in the range of 500-1000°C, which is beneficial to increasing the specific surface area of the carbon material block.
[0058] Example 8 The difference from Example 2 is that in step 1, the polystyrene resin and the zinc oxide powder are directly mixed under heating conditions without the involvement of a solvent. That is, in step 1, 7 g of polystyrene resin and 5 g of zinc oxide powder (particle size 50 nm) are mixed in an internal mixer at 110 °C for 10 min until an apparently uniform milky white product is obtained. The specific surface area of the obtained three-dimensional porous carbon block material is 790 m 2 / g.
[0059] Comparing Example 2 with Example 8, the direct mixing method is more concise and efficient, and has high production efficiency, but the mixing uniformity of the polymer material and the pyrolysis auxiliary agent is not as good as the liquid phase mixing method in the solvent.
[0060] Example 9 A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1: Take 6.5 g of the recycled polyethylene and mix it with 5 g of zinc nitrate hexahydrate powder in toluene, stir and heat to 80 °C until the solvent is completely evaporated to obtain a white solid mixture; Step 2: placing the mixture obtained in step 1 into a micro injection molding machine for injection molding into a cuboid precursor; Step 3: The precursor obtained in step 2 is placed in a tubular furnace for pyrolysis, using argon as the protective gas with a flow rate of 100 mL / min and a heating rate of 5 °C / min. After heating to 1200 °C and keeping the temperature for 2 h, a rectangular three-dimensional porous carbon block material can be obtained after natural cooling.
[0061] The three-dimensional porous carbon material block product finally obtained in Example 9 can maintain the geometric shape of the precursor. According to the nitrogen adsorption and desorption test, the specific surface area of the carbon material obtained in Example 9 is 370 m 2 / g.
[0062] Comparing Example 4 with Example 9, the carbon product obtained from zinc nitrate has a higher specific surface area, and nitrogen atom doping can be easily introduced during the preparation process, which is beneficial for applications in the fields of electrochemical energy storage and catalysis.
[0063] Comparative Example Comparative Example 1 Powdered porous carbon materials were prepared by direct pyrolysis of lignin.
[0064] The powdered porous carbon material prepared in Comparative Example 1 was used as the active material, conductive carbon black was used as the conductive agent, sodium carboxymethyl cellulose was used as the binder, the mass ratio of the three was 7:2:1, copper foil was used as the current collector, and it was cut as the negative electrode. Sodium metal was used as the positive electrode, the electrolyte was 1 mol / L NaPF6 ethylene carbonate / diethyl carbonate (volume ratio of 1:1) solution, and glass fiber filter paper was used as a diaphragm. It was assembled into a CR2025 sodium ion button battery in an argon atmosphere glove box. As a control, the disc-shaped porous carbon material obtained in Example 1 was directly used for the sodium ion battery block negative electrode to assemble a sodium ion battery.
[0065] Figure 4 The sodium ion battery cycle performance and rate performance of Example 1 and Comparative Example 1 are compared, and the test voltage window is 0.01-3.00 V. At a current density of 1A / g, the charge and discharge specific capacity of the bulk porous carbon obtained in Example 1 is stable at about 200 mAh / g, the coulombic efficiency is about 100%, and the specific capacity remains at 170 mAh / g after 4000 charge and discharge cycles; the powder porous carbon material fired without zinc-based auxiliary agent in Comparative Example 1 has a capacity of about 100 mAh / g, and the performance drops sharply after 2000 charge and discharge cycles, and has basically no electrochemical sodium storage performance after 3000 cycles. Therefore, the three-dimensional porous carbon bulk electrode material prepared by pyrolysis of zinc-based auxiliary agent has higher specific capacity and better cycle performance.
[0066] Comparative Example 2 The difference from Example 1 is that the zinc oxide powder is replaced by metal zinc powder. The details are as follows: A method for preparing a three-dimensional porous carbon block electrode based on a polymer material, the steps are as follows: Step 1. Take 6 g of polyacrylonitrile-polybutadiene-polystyrene copolymer resin, mix it with 5 g of metal zinc powder in N,N-dimethylformamide, stir and heat to 100 °C until the solvent evaporates to obtain a milky white block solid; Step 2. Pressing the solid mixture obtained in step 1 into a disc-shaped precursor using a tablet press at room temperature; Step 3. Place the cylindrical precursor obtained in step 2 in a tubular furnace for pyrolysis, using argon as the protective gas with a flow rate of 50 mL / min. Heat to 1200 °C and keep warm for 2 h. After natural cooling, a disc-shaped three-dimensional porous carbon block material can be obtained.
[0067] The precursor obtained in Comparative Example 2 can be processed into a disc-shaped geometric shape, but it deforms and collapses after melting during the pyrolysis process, and the final three-dimensional porous carbon material product cannot maintain the geometric shape of the precursor. Further increasing the proportion of zinc powder in the precursor to 90% can improve the shape stability and performance of the porous carbon block material obtained (compared to patent CN111825078B), but the melt processability of the polymer precursor will be lost, and it is difficult to process it into a custom target shape by casting, extrusion, injection molding, calendaring, etc.
[0068] Figure 5 This is a scanning electron microscope image of the three-dimensional porous carbon product prepared in Comparative Example 2. Due to the low content of metal zinc powder, sufficient space occupation and pore formation cannot be achieved. Figure 5 The morphology of the porous carbon block material obtained is poorly regular. The part not occupied by zinc presents a granular carbon structure. The part in contact with zinc powder forms unconnected pits and holes, which is not conducive to the rapid transmission of electrolyte. The carbon layer wall is thick, which is not conducive to the deintercalation of ions. According to the nitrogen adsorption and desorption test, the specific surface area of the carbon material obtained in Comparative Example 2 is 58 m 2 / g, the specific surface area is relatively small, and it is difficult to play a significant role in electrochemical energy storage, catalysis, molecular adsorption and other fields.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a three-dimensional porous carbon block electrode based on polymer materials, characterized in that: The following steps are involved: A carbon source is mixed with a pyrolysis auxiliary agent to prepare a block precursor with a custom target shape; the block precursor is heated to above 1000°C in a protective atmosphere to obtain a three-dimensional porous carbon material block with a custom target shape; the carbon source is a thermoplastic polymer, and the pyrolysis auxiliary agent is selected from one or more of zinc group metal oxide powder, zinc group metal nitrate powder, and zinc group metal carbonate powder.
2. The method for preparing a three-dimensional porous carbon block electrode based on a polymer material according to claim 1, characterized in that: The thermoplastic polymer is selected from one or more of polyethylene, polypropylene, polybutadiene, polyisoprene, polystyrene, polyacrylate, polylactic acid, polyacrylonitrile-polybutadiene-polystyrene copolymer / blend, and thermoplastic polyurethane.
3. The method for preparing a three-dimensional porous carbon block electrode based on a polymer material according to claim 1 or 2, characterized in that: The particle size of the pyrolysis auxiliary agent is 10nm - 100μm.
4. The method for preparing a three-dimensional porous carbon block electrode based on a polymer material according to claim 1, characterized in that: The carbon source is directly mixed with the pyrolysis auxiliary agent to produce a bulk precursor with a custom target shape.
5. The method for preparing a three-dimensional porous carbon block electrode based on polymer material according to claim 1, characterized in that: The carbon source and the pyrolysis auxiliary agent are fully mixed in an organic solvent and then dried to form a bulk precursor with a customized target shape.
6. The method for preparing a three-dimensional porous carbon block electrode based on polymer material according to claim 5, characterized in that: The organic solvent is selected from one or more of methanol, ethanol, acetic acid, ether, ethyl acetate, ethylene glycol, isopropanol, n-butanol, isobutanol, propyl ether, acetone, tetrahydrofuran, n-hexane, cyclohexane, heptane, isooctane, petroleum ether, benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
7. The method for preparing a three-dimensional porous carbon block electrode based on polymer material according to claim 1, 4 or 5, characterized in that: Bulk precursors can be made into custom target shapes by casting, compression molding, extrusion, injection molding or calendaring.
8. The method for preparing a three-dimensional porous carbon block electrode based on polymer materials according to claim 1, characterized in that: The protective atmosphere is selected from one or more of nitrogen, argon and helium.
9. The method for preparing a three-dimensional porous carbon block electrode based on polymer material according to claim 1 or 8, characterized in that: The mass ratio of carbon source to pyrolysis auxiliary agent is (0.8-1.5):
1.
10. The method for preparing a three-dimensional porous carbon block electrode based on polymer materials according to claim 1, characterized in that: Raise the temperature to 1100-1200 ℃ at a rate of 3-20 ℃ / min and keep it at this temperature for 2-3 h.
Citation Information
Patent Citations
Method for preparing porous carbon material by using porous copper as template
CN103738935A
Cited By
Preparation method of silicon-carbon negative electrode material based on organic matter pyrolysis modified porous carbon
CN119706807A
Volatile alcohol detection sensor as well as preparation method and application thereof
CN121385059A